Interdisciplinary approach to patients with psoriatic arthritis: a prospective, single-center cohort study - Groß, Georg; Lull, Christian; Ahnen, Jan von; Blauth, Mara; Schwaan, Johanna; Olsavszky, Victor; Schmieder, Astrid; Leipe, Jan (Therapeutic advances in chronic disease, 2024)
Background: Psoriatic arthritis (PsA) is a chronic systemic inflammatory disease that affects up to 30% of patients with psoriasis. Diagnosis and treatment could be improved by implementing an interdisciplinary dermatological-rheumatological consultation (IDRC). - Objectives: This study aimed to assess the effect of a face-to-face IDRC involving both a dermatologist and a rheumatologist evaluating patients in a single visit, on disease activity and burden in patients with PsA. - Design: Prospective, single-center, cohort study. - Methods: 202 patients with psoriasis were enrolled, among whom 115 individuals with psoriasis and musculoskeletal symptoms underwent an IDRC. Disease manifestations, comorbidities, and both objective and subjective disease activity scores were evaluated. - Results: Out of the participants, 56 were diagnosed with definite PsA, while the remaining 146 had psoriasis. Nail involvement was associated with axial PsA (odds ratio 4.11; 95% CI 1.22-13.82; p = 0.02). Patients with PsA often experienced a prolonged time to diagnosis (mean 187 weeks) and had a significant psychosocial burden (mean Hospital Anxiety and Depression Index Scale [HADS]-Anxiety score of 7.66 and mean HADS-Depression score of 5.63). Post-IDRC, both objective and subjective disease parameters showed improvement, and patients required less time for consultations with healthcare professionals compared to before the IDRC. - Conclusion: These findings suggest that an IDRC approach could effectively expedite and optimize the diagnosis and treatment of patients with psoriasis and musculoskeletal symptoms.
Erstmals veröffentlicht: 28. November 2024
Gesehen am 18.03.2025